Knowledge of menopause among women at the Nallur MOH area - Piraveena, S.; Sharmila, D.; Kamalarupan, L.; Nivetha, K. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Menopause is permanent cessation of menstruation. It will cause physical and psychological symptoms which affect the well-being and quality of life of middle-aged women. Knowledge on menopausal symptoms, consequences and management may improve the quality of peri and postmenopausal women's lives. Objective: To assess the knowledge on menopause among women in the Nallur MOH area. Methodology: Community based cross sectional study design used to collect the data from 426 women who aged between 40 to 60 years in Nallur MOH. Semi-structured interviewer administered questionnaire was used to collect the data. Data was analyzed using SPSS and presented in tables and diagrams. Ethical approval was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. Results: Mean age of participants was 50.88 years (SD=6.046). Almost all the participants of this study were Tamil, among them most of the participants (82.5%) were Hindu. Around 79.8% of the participants were married and most of them (56.8%) were housewives. More than half of participants (63.7%) had moderately adequate knowledge on menopause. All the participants knew the meaning of menopause and also the majority of them (93.4%) knew the menopausal age range. Majority of the participants (84.5%) considered that menopause is a normal body process. Most of the participants knew that joint and muscular discomfort (75%), weight gain (64%) and irritability (51.5%) are menopausal symptoms. However, the majority of them did not know that hot flushes (80.6%), anxiety (75.75%), inner restlessness (62%) and decreased memory (61.75%) are menopausal symptoms. Majority of the participants (71%) knew that osteoporosis is a long-term consequence of menopause. Majority participants knew that eating a calcium rich diet (76.75%) will help to cope up with menopausal symptoms. Relatives were the main source of information regarding the menopause. Conclusion: Most of the participants had moderately adequate knowledge
Keywords: Menopause; Knowledge